Develop organizational learning capabilities within knowledge management processes (Applied research in the General Company of Iraqi Airways) - Rahman Tahir, Abdal; Mahmud, Khawam (Opción, 2019)
The current research aims to identify the degree to which knowledge manage- ment processes (knowledge Creation, knowledge distribution, knowledge inter- pretation, knowledge implementation), and the availability of organizational learning capabilities (adaptive learning capacity and the ability to learn cons- tructively) in the Iraqi airline company. In addition to determining the level of impact of knowledge management processes in the development of organizatio- nal learning capabilities, to achieve the objective of the research, the views of a sample of individuals in the General Company of Iraqi Airways, which amoun- ted to (30) individuals by adopting the questionnaire as a main tool in collecting data and information, and analyzed their responses using many methods (Mean, standard deviation, correlation coefficient, and simple regression coefficient) based on the SPSS program. The results of the research are based on a number of conclusions, the most important of which is that the knowledge management processes are one of the basic building blocks of the company’s operations. It also plays an important role in the development of organizational learning capa- bilities. And the response variable (organizational learning abilities), all of which were positive and functionally significant. The main recommendations of the study are to adopt the proposed model presented by the research, which shows the relationship and impact of knowledge management processes in organizational learning capabilities at all levels of the company. And work on the development of systems and regulations that stimulate and encourage human resources to practice knowledge processes and assimilate the experien- ces of the company through experimentation, observation and analysis, and then creativity and innovation for the purpose of developing organizational learning capabilities in the company.